2006
DOI: 10.1111/j.1475-6773.2006.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of New Insurance Coverage on the Health Status of Low‐Income Children in Santa Clara County

Abstract: Objective. To examine whether providing health insurance coverage to undocumented children affects the health of those children. Data Sources/Study Setting. The data come from a survey of 1235 parents of enrollees in the new insurance program (“Healthy Kids”) in Santa Clara County, California. The survey was conducted from August 2003 to July 2004. Study Design. Cross‐sectional study using a group of children insured for one year as the study group (N=626) and a group of newly insured children as the compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…Prior studies found insurance coverage improves self-reported perceived health status and reduce activity limitations in children 12,14. We differ from these studies in two aspects.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Prior studies found insurance coverage improves self-reported perceived health status and reduce activity limitations in children 12,14. We differ from these studies in two aspects.…”
Section: Discussioncontrasting
confidence: 62%
“…These studies have reported changes in utilization at both the national9 and state levels 10-12. They also point to the importance in the continuity in insurance coverage, which in our population was accounted for by looking at access across the three year study period 13.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In a study comparing children continuously insured by Health Kids for 1 year and a group of newly insured children, the study group was significantly less likely to be in fair/poor health and to have functional impairments than the comparison group of newly insured children (15.9% vs 28.5% and 4.5% vs 8.4%, respectively). Impacts were largest among children who enrolled for a specific medical reason [95]. Overall, the fundamental principal of these local initiatives is that children should not be without health insurance because it is a societal responsibility to keep all children healthy and well.…”
Section: Access To Health Carementioning
confidence: 98%